KEGIATAN DHARMA YATRA PADA MASYARAKAT DESA LOKAPAKSA KE PURA BATUR - Ida Ayu Dwidyaniti Wira (Jurusan Dharma Acarya STAHN-TP Palangka Raya, 2020)
The awareness of human life can only be achieved if man can return to his identity as a human being who is an individual creature, a social being and a servant of God and harmonizes each of these relationships so that it continues to be in harmony and balance. In Hinduism this concept is called Tri Hita Karana. In carrying out Dharma yatra activities for the people of Lokapaksa Village to Pura Batur. This is a milestone in the spiritual awakening of Hindus who have long been shackled by customs and culture without being able to understand more deeply about the nature of dharma teachings. This research is in the form of a qualitative design in which data is collected using observation techniques, a way to collect data through direct observation. Data were analyzed using qualitative methods. Based on the analysis, the conclusions from the research results are as follows: The Lokapaksa Village community carries out Dharma Yatra activities, able to form intelligence, namely: intellectual intelligence (IQ). Emotional intelligence (EQ), and spiritual intelligence (SQ). These three intelligences are gifts from God Almighty that must be utilized simultaneously and optimally. In this case, the attitude of the Lokapaksa Village community is able to improve, namely: (1) Attitudes to foster social sensitivity, (2) attitudes to increase self-discipline, (3) reduce materialistic attitudes. Of these three things are the spiritual goals of life to get closer to God and religious practices or religious rituals. The educational values ​​contained in Dharma Yatra activities are: tattwa values, moral values, ceremonial values.